Pengembangan E-Module Pendidikan Seksual Dalam Implementasi Pembelajaran Mendalam Anak Usia Dini - Asyriyah Asis; Herlina Herlina; Rusmayadi Rusmayadi; Azizah Amal; Salma Samputri (JURNAL MANAJEMEN PENDIDIKAN, 2026)
DEVELOPMENT OF A SEXUAL EDUCATION E-MODULE IN THE IMPLEMENTATION OF DEEP LEARNING FOR EARLY CHILDHOOD EDUCATION The increasing number of child sexual abuse cases has become a serious challenge that requires preventive efforts through sexual education from an early age. However, the implementation of sexual education in Early Childhood Education (ECE) institutions still faces various challenges, including teachers' limited competencies, the lack of systematic teaching materials, and the absence of digital learning media that support the implementation of deep learning. This study aims to develop a sexual education e-module for Early Childhood Education teachers that meets the criteria of validity, practicality, and effectiveness in supporting the implementation of deep learning. This study employed a Research and Development (R&D) approach using the Four-D (4D) model, consisting of the define, design, develop, and disseminate stages. The research participants were teachers from two Early Childhood Education institutions. Data were collected through observations, interviews, questionnaires, expert validation, and teacher comprehension tests. The data were analyzed using descriptive quantitative and qualitative methods. The findings indicate that the developed e-module was categorized as highly valid based on expert evaluations, highly practical based on teachers' responses, and effective in improving teachers' understanding of sexual education for young children. The developed product supports the implementation of deep learning by providing systematic, contextual, interactive, and child protection-oriented learning materials. Therefore, the e-module is suitable for use as a digital learning medium to enhance teachers' competencies in implementing sexual education in Early Childhood Education.